PEMBERIAN HIJAUAN PAKAN TERNAK YANG DIPOTONG SEBAGAI PAKAN TERNAK RUMINANSIA YANG DI KANDANGKAN DI KECAMATAN WEAPO KABUPATEN BURU - Eoh, Marna; Rehatta, Lea Marlyn (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This research aimed to determine the pattern of providing cut green forage for ruminants raised in confinement. The research employed a survey method through interviews and direct field observations. A total of 30 respondents were selected using purposive sampling, representing three sample villages in Waeapo District, namely, Waenetat, Waekasar and Wanareja. The results showed that the provision of green forage reached 47.00%, while in terms of feeding practices, 100% of farmers were able to utilize the available forage as animal feed.